Hydraulic evaluation of energy dissipation in four types of buffer basins, under variable flow conditions [Evaluación hidráulica de la disipación de energía en cuatro tipos de cuencos amortiguadores, bajo condiciones de flujo variable] - Vásquez, Luis (2019)
ABSTRACT The present investigation is focused on experimentally determining the dissipation of hydraulic energy for different types of buffer basins. For this purpose, a series of tests were developed in the laboratory under six flow conditions, so that six experimental data per bowl were obtained. The structures under study are type I, II, III and IV bowls according to the classification of the U.S. Bureau of Reclamation; bowls that dissipate energy mainly by the formation of the hydraulic shoulder and secondly by the presence of deflector dies, impact blocks and exit thresholds. Each bowl has been designed and sized according to the characteristics of the variable slope channel, for flow conditions tested with Froude numbers between 4,08 and 5,99. Finding that the type III damper bowl is the one that best dissipates the energy with the shortest bowl length for flows close to the design, with the disadvantage that the length of the hydraulic shoulder for flow rates far beyond exceeds the length of the bowl; while for all the flow rates tested, the type IV damping bowl presents the highest values of energy dissipation with hydraulic projections formed inside the bowl, with a better return of flow downstream.